Infection among adult small bowel and multivisceral transplant recipients in the 30‐day postoperative period. Issue 5 (28th June 2013) - Primeggia, J.; Matsumoto, C.S.; Fishbein, T.M.; Karacki, P.S.; Fredette, T.M.; Timpone, J.G.
Abstract: Background: Intestinal transplantation is a potential option for patients with short gut syndrome (SGS), and infection is common in the postoperative period. The aim of our study was to identify the incidence and characteristics of bacterial and fungal infections of adult small bowel or multivisceral (SB/MV) transplantation recipients in the 30‐day postoperative period. Methods: This retrospective chart review assessed the incidence and characteristics of bacterial and fungal infections in patients who underwent SB/MV transplant at our center between April 2004 and November 2008. Patient data were retrieved from computerized databases, flow‐charts, and medical records. Results: A total of 40 adult patients with a mean age of 38.7 ± 13.4 years received transplants during this period: 27 patients received isolated SB, 12 received MV, and 1 received SB and kidney. Our immunosuppressive regimen included basiliximab for induction, and tacrolimus, sirolimus, and methylprednisolone for maintenance therapy. The most common indications for transplant were SGS, intestinal ischemia, Crohn's disease, trauma, motility disorders, and Gardner's syndrome. We report a 30‐day postoperative infection rate of 57.5% and mean time to first infection of 10.78 ± 8.99 days. A total of 36 infections were documented in 23 patients. Of patients who developed infections, 56.5% developed 1 infection, 30.4% developed 2 infections, and 13% developed 3 infections. The most common site of infection was the abdomen, followed by blood, urine, lung, and wound infection. The isolates were gram‐negative bacteria in 49.3%, gram‐positive bacteria in 39.4%, and 11.3% were fungi. The most common organisms were Pseudomonas (19%), Enterococcus (15%), and Escherichia coli (13%). Overall, 47% of infections were due to drug‐resistant pathogens; 31% of E. coli and Klebsiella species were extended‐spectrum beta‐lactamase‐producing organisms, 36% of Pseudomonas was multidrug resistant (MDR), 75% of Enterococcus was vancomycin resistant, and 100% of Staphylococcus aureus was methicillin resistant. Conclusion: These findings demonstrate that bacterial and fungal infections remain an important complication in SB/MV transplant recipients within the early postoperative period. Infections due to MDR organisms have emerged as an important clinical problem in this patient population.